(untitled) (Journal of Asian Development Studies, 2024)
The study was conducted to investigate the role of consumer behavior in stimulating the intention to adopt e-banking services under the moderation of financial literacy. Further it aimed at gaining an in-depth view of the factors that lead to e-banking implementation, such as perceived security, financial attitude, and financial literacy. Using a deductive approach, the study collected data through a structured questionnaire given to 140 internet banking users in Lahore, who had been sampled using a convenience sampling method. Structural equation modeling was utilized to investigate the research hypotheses and to examine customer behavior and levels of financial literacy. The investigation throws much emphasis on the role of financial literacy as a moderating variable in technology adoption models. By explaining its significance in the acknowledgement of e-banking services, the research provides meaningful insights into consumer behavior within the realm of digital banking, therefore aiding in the formulation of successful strategies for e-banking adoption. Findings indicate that security perception, financial attitude, and financial literacy directly impact the intention to use an online banking service. With higher financial literacy, better financial attitudes will contribute positively to the adoption of e-banking, and improving the financial knowledge of customers will act as a stimulating agent for the usage of e-banking services.